Identification of lung disease types using convolutional neural network and VGG-16 architecture - Сайфул Бухорі; Бангкіт Юдхо Негоро Верді; Юліа Ретнані Вінді Ека; Аді Путра Януар (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï, 2023)
Pneumonia, tuberculosis, and Covid-19 are different lung diseases but have similar characteristics. One of the reasons for the worsening of disease in lung sufferers is a diagnosis that takes a long time. Another factor, the results of the X-ray photos look blurry and lack contracture, causing different diagnostic results of X-ray photos. This research classifies lung images into four categories: normal lungs, tuberculosis, pneumonia, and Covid-19 using the Convolutional Neural Network method and VGG-16 architecture. The results of the research with models and scenarios without pre-trained use data with a ratio of 9:1 at epoch 50, an accuracy of 94%, while the lowest results are in scenarios using data with a ratio of 8:2 at epoch 50, non-pre-trained models, accuracy by 87%.